Neural responsivity to food cues varies with food fussiness in adolescents - Sarah Ann Duck; Elena Jansen; Liuyi Chen; Shuxian Hua; Allison Ahn; Leora Benson; Afroditi Papantoni; Susan Carnell (Scientific Reports)
Abstract Food fussiness (picky eating) increases risk for poor nutrition and eating disorders but its biological underpinnings are not understood. We aimed to investigate behavioral (observed as well as parent- and self-reported), and neural (using functional Magnetic Resonance Imaging (fMRI)) correlates of food fussiness. Adolescents completed an fMRI task during which they viewed photos of fruits and vegetables [F&V], high energy-density [High-ED] foods, and Non-foods. Following scanning, they completed a multi-item ad libitum meal [ALM], then an Eating in the Absence of Hunger [EAH] test. Parents completed the Child Eating Behavior Questionnaire [CEBQ]. Adolescents reported habitual dietary intake using a 24-hour dietary recall (ASA24). Adolescents were categorized based on CEBQ Food Fussiness [FF] scores, such that scores ≥ 3 = high FF (n = 23), and scores ≤ 2 = low FF (n = 28). The high vs. low FF group reported lower wanting for F&V stimuli in the fMRI task and consumed lower absolute and relative intake of F&V at the ALM, while ASA24 data also demonstrated greater % total kcal intake from added sugar. Adolescents with high FF demonstrated activation that was consistent with decreased approach toward F&V and increased approach toward High-ED foods. Neuroimaging results demonstrated differential responses to F&V and high-ED stimuli among adolescents with high food fussiness, providing preliminary evidence for a neural signature of food fussiness.